OBSTACLES AND CHALLENGES OF INDONESIA'S MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) IN FACING THE COVID-19 PANDEMIC - Agoes Djatmiko; Elisabeth Pudyastiwi (Universitas Pendidikan Ganesha, 2020)
The Covid-19 pandemic has led to shifts and changes in consumer purchasing patterns. Usually, even though there are online sales, many consumers still buy products directly to shops or shopping centers. But now, because there are restrictions and government regulations not to leave the house, consumers automatically do not allow it to stay outside the house for long. MSME players must also adjust and condition the sales of their products and services. It is necessary to improve product quality and service adjustments to attract consumers. The Covid-19 pandemic that occurred in Indonesia had an impact on economic instability, especially on MSMEs. These UMKM players feel a direct impact in the form of a decrease in sales turnover. For this, MSMEs players must have a strategy to survive in the midst of this pandemic and are required to be able to adapt to the conditions that occur